Pemodelan Electronic Load Controller Pada Beban Pembangkit Listrik Tenaga Mikro Hidro Merasap - Kunek, Kornelius (ELKHA : Jurnal Teknik Elektro, 2015)
Abstract– Energi Baru dan Terbarukan (EBT) or New and Renewable Energy is one of the alternative energies purported to tackle the problems of energy shortage in Indonesia. Sometimes the voltage generated by the hydropower is inconstant that it can speed up damages to electronic appliances. Thus, installing a device of Electronic Load Controller (ELC) is necessary to control the current, frequency, and hydropower voltage as it can nominally maintain the constant voltage despite the unstable consumer electricity load. ELC is often used in both hydropower and PLTMH because it is more affordable than other protective devices. This study project was conducted in Merasap PLTMH, Bengkayang-Indonesia, where a simple ELC was modeled and simulated whenever the consumer electricity load changes. ELC simulation result displayed in Matlab program showed that ELC can control the burden on consumers when reaching a peak load of up to 9850 W with a frequency of 48.56 Hz, meanwhile, it decreased the consumer load of up to150 W with a frequency of 50.51 Hz. While the data of Merasap PLTMH during the peak load of 9850 W with a frequency of 50.76 displayed a decrease in burden on consumers’ load of up to 150 W with a frequency of 50.51. Therefore, based on the comparison results obtained, it can be concluded that the ELC simulation can work significantly in stabilizing consumer electricity load. Keywords– Electronic Load Controller (ELC), Micro Hydro Power (MHP), ELC Simulation